Araguspongine: an indole alkaloid as panc-1 cell inhibitory adapted to nutrient starvation from Indonesian's marine sponge spongionellapulchella. (December 2018) - Kurnianda, V; Syahliza, F; Karina, S; Agustina, S; Ulfah, M; Octavina, C; Mardiah, A; Ramadhan, M R; Purnawan, S
Abstract: Isolation of active metabolite from Indonesian's Marine Sponge Spongionellapulchella has been conducted on July 2018. Active compound isolated based on bioassay-guided separation with several steps of chromatography. The rate of viability shows that IC50 = 0.2 μg / mL against PANC-1 cell. The active compound know as C28 H51 N2 O2 determined by LCMS-ESI with molecular weight [M+H] + 447.3951m/z. Based on the FTIR spectrum shows that the active metabolite has functional groups at 3435.56 cm 1 as N-H secondary amines, 2853.39 cm 1 as C-H methyl, 2769.64 cm 1 as C-H methylene and the fingerprint region of amine at 1637.27 cm 1 as C-N imine. The active compound which knows as araguspongine, an indole alkaloid shows potential activity against PANC-1 cell.